Etchless Fabrication of High‐Quality Refractory Titanium Nitride Nanostructures. Issue 7 (5th May 2021) - Panos, Stavros; Tselekidou, Despina; Kassavetis, Spyros; Fekas, Ilias; Arvanitidis, John; Christofilos, Dimitris; Karfaridis, Dimitrios; Dellis, Spilios; Logothetidis, Stergios; Patsalas, Panos
Abstract : Nanosphere lithography has emerged as an efficient route to produce plasmonic nanostructures. Herein, the processes of nanosphere lithography and reactive magnetron sputtering that seem incompatible for a variety of reasons are reviewed and explained. However, understanding the physical obstacles of this combination enables us to identify a window of process parameters that make the deposition of well‐defined trigonal nanoislands of titanium nitride (TiN) feasible. TiN is used as a case study because it is a very good representative of refractory conductive nitrides, such as ZrN, HfN, NbN, and TaN. A UV ozone step is used to confine the triple‐junction vias of the polystyrene mask, and the reactive magnetron sputtering parameters are fine‐tuned to increase the directionality of deposited species, in particular the substrate‐to‐target distance is maximized to improve geometrical directionality, and a negative bias voltage is used to guide the ionic species deep into the vias. The proposed process produces well‐defined TiN nanoislands with low concentration of point defects that have similar structure with continuous films of high electrical conductivity and plasmonic performance. Abstract : Nanosphere lithography (NSL) is an efficient route to produce plasmonic nanostructures. Herein, the NSL processes and reactive magnetron sputtering that seem incompatible for a variety of reasons are reviewed. Understanding the physical obstacles of this combination enables us to identify the process parameters that make the deposition of well‐defined nanoislands of the emerging plasmonic TiN feasible.